Hidden order behind the cooperation. (1st December 2021) - Wei, Junjie; Han, Dun
Abstract: Cooperation is ubiquitous in human as well as animals societies, however, the study of the driving forces behind cooperation is still an open question. Thus, exploring the hidden order related to cooperation has become a hot issue recently. Fortunately, evolutionary game theory and network science provide some new research perspectives for the cooperative behavior. In this letter, we focus on the present study of cooperation mechanism, and further put forward some feasible research prospects from the perspective of evolutionary game by arranging and researching the thread of history. Specifically, we first summarize the cooperation research status from the aspects of network topology and individuals' strategy updating rules etc., and we then discuss the hidden order behind the emergence and maintenance of cooperation, the development trends are presented in the last.